การบูรณาการการเรียนการสอนกับการสื่อสารเพื่อใช้ประโยชน์งานวิจัย: “ส้มโอโมเดล” - หรุ่นเกษม, นิษฐา (Area Based Development Research Journal, 2018)
This research project aims to develop media for local community's development and problem solving in Nakhon Pathom with the information from Thai Research Fund's (TRF) research database and integrate such information and media in the Pomelo model. The methodology used in this project is participatory communication with 3 stages, including 1) the pre-development stage of the media, 2) the media development stage, and 3) the post-media development stage. The research population covered 3 groups of stakeholders: the academic team, the community team, and the student team. The samples of the academic team were chosen using a selective approach from the lecturers in the field of Communication Arts, Faculty of Management Science, Phranakhon Rajabhat University, consisted of 10 lecturers. For the community team, the researchers applied the snowball sampling technique to identify the sample group, consisted of the Pomelo gardeners in the area of Rai Khing municipality and the knowledgeable people in the community. For the student team, a purposive method was used in the researcher's classes for the third year students, consisted of 7 groups. The development of the media to communicate TRF's research in Nakhon Pathom can be summarized that the media have been developed by the students in various forms such as infographics, comic books, pop-up cards, posters, comment picture for Line and Instagram, radio spot, TV spot and online video clips. The evaluation of the media quality and benefits for the community suggests that the users are satisfied with the media because it can be used in the community. In the learning process of the Pomelo model, the students also improved their knowledge and skills, and were satisfied.